Effect of type of underlay film on fermentation profile, nutritional quality and estimated loss of organic matter in the outer layer of whole‐plant maize ensiled in large bunker silos. (7th February 2017) - Wang, K.; Uriarte, M. E.; Li, S. C.; Rich, K.; Banchero, C.; Bu, D. P.; Wilkinson, J. M.; Bolsen, K. K.
Abstract: Losses of organic matter in the outer layers of bunker silos covered with conventional polyethylene (PE) plastic can be substantial due to oxygen transmission through the plastic top‐covering film during the post‐ensiling storage period. The effect of two silo covering materials, oxygen barrier (OB) film (45 μm thickness) and clear PE film (50 μm thickness), as underlays to a white‐on‐black PE plastic top cover (120 μm thickness), was assessed in the outer layer of whole‐plant maize silage stored in three large bunker silos in the People's Republic of China. Samples of the crop at harvest and of silage from the upper 45 cm layer at 5 months post‐ensiling, prior to removal of silage for feed‐out, were analysed for DM, fermentation profile and chemical composition. Loss of OM was estimated from concentrations of ash in the crop at harvest and in the silage. Differences between underlay films in silage fermentation profile were small. Silage protected with OB underlay film had higher mean concentration of starch ( p  <   .008) and higher mean NDF digestibility ( p  <   .003) than silage under PE underlay film. Concentrations of ash were lower ( p  <   .001) for silage covered with OB film than for PE film in all three trials. Mean estimated losses of OM were 170 g/kg for OB underlay film and 232 g/kg for PE underlay film ( p  <   .001), and whole‐silo estimated net economic benefits to OB underlay film ranged from 0.17 to 0.74 US $ per tonne fresh crop ensiled.